POTENSI PROBIOTIK DALAM TATALAKSANA ORAL CANDIDIASIS: Ulasan Sistematik - Fitriasari, Nuri; Wahyuni, Indah Suasani (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
Background: Probiotics are living microorganisms which when given in sufficient quantities will provide health benefits to humans. The role of probiotic bacteria in the oral environment is to prevent attachment of pathogenic bacteria, produce antimicrobial substances, activate and regulate the immune response. Today probiotics are recommended for oral health maintenance and management of oral diseases, one of which is Oral Candidiasis. The purpose of this paper is to describe the potential of probiotics in the management of Oral Candidiasis.Method: Systematic literature review used literature search methods in electronic databases: Google Scholar, Science Direct, and PubMed. The keywords were